Take the mummy and run : the Riot Brothers are on a roll - Amato, Mary.; Long, Ethan (New York : Holiday House, 2009)
Brothers Orville and Wilbur Riot set off on a whole new set of adventures which include hunting for lost mummies and creating their own water park.
The Riot Brothers solve a mystery -- The Riot Brothers find a lost mummy -- The Riot Brothers have fun at a water park -- Bonus!
"Bonus fun and games inside!"--Dust jacket.
3.8
3-6
Keywords: Brothers -- Juvenile fiction; Cousins -- Juvenile fiction; Summer -- Juvenile fiction; Brothers -- Fiction; Cousins -- Fiction; Humorous stories; Summer -- Fiction; Brothers -- Fiction; Cousins -- Fiction; Humorous fiction; Summer -- Fiction; Humorous stories